Analisis Board Game “Everdell” : Ditinjau Dari Strategi Desain Visual Dan Dampaknya Terhadap Pemain - Reza Muhammad Ilham Prakoso (VisArt: Jurnal Seni Rupa dan Design, 2024)
The board game industry has now become something that is popular with people from children to adults. Game flow mechanics are crucial to the experience for players. However, attractive visuals are also very important for the playing experience. How the world in the game works, how time rotates in the game. Therefore, the steps that must be taken as a designer or artist in a board game are no less important than the game flow mechanics. This research uses an interview method with the artist who created the Everdell board game, Andrew Bosley. The results of this research show what steps were taken in creating the Everdell board game. What are the challenges as a board game designer? This study aims to find out how to build the right visuals to attract the player's attention and bring the player into the world of the game. This research shows the importance of designing appropriate visual communication as a strategy to strengthen the concept of gameplay in a board game. It is hoped that the achievements and targets of this research will be able to contribute to the development of board games